Co-production and Criminal Justice - Johns, Diana (Criminology in Focus, 2023)
This book explores practical examples of co-production in criminal justice research and practice. Through a series of seven case studies, the authors examine what people do when they co-produce knowledge in criminal justice contexts: in prisons and youth detention; with criminalised women; from practitioners' perspectives; and with First Nations communities. Co-production holds a promise: that people whose lives are entangled in the criminal justice system can be valued as participants and partners, helping to shape how the system works. But how realistic is it to imagine criminal justice 'service users' participating, partnering, and sharing genuine decision-making power with those explicitly holding power over them? Taking a sophisticated yet accessible theoretical approach, the authors consider issues of power, hierarchy and different ways of knowing to understand the perils and possibilities of co-production under the shadow of 'justice'. In exploring these complexities, the book brings cautious optimism to co-production partners and project leaders. This book provides a foundational text for scholars and practitioners seeking to apply co-production principles in their research and practice. With stories from Australia, the UK and Ireland, the text will appeal to the international community. For students of criminology and social work, especially practitioners and/or those with lived experience of criminal justice entanglement, the book's critical insights will enhance their work in the field.